DEVELOPMENT AND VALIDATION OF THE CROHN'S DISEASE-HEALTH INDEX (CD-HI), A CLINICALLY-RELEVANT, DISEASE-SPECIFIC PATIENT-REPORTED OUTCOME MEASURE. (22nd January 2022) - Seabury, Jamison; Weinstein, Jennifer; Rosero, Spencer; Varma, Anika; Wagner, Ellen; Zizzi, Christine; Dilek, Nuran; McDermott, Michael; Kaat, Aaron; Saubermann, Lawrence; Temple, Larissa; Rogoff, Scott; et al.
Abstract: STUDY AIM: The goal of this research is to develop and validate a novel, disease-specific patient-reported outcome measure (PROM) for use in clinical monitoring and therapeutic trials of Crohn's Disease (CD). BACKGROUND: With approximately 780, 000 cases of CD in the U.S., it is important to have a comprehensive, sensitive, and reliable disease-specific PROM that accurately indicates patient function, perceived health, and quality of life. Moreover, as clinical trials are planned for individuals with CD, a valid PROM is vital to determine the overall effect of potential treatments on patient disease burden. This research describes the construction and testing of the Crohn's Disease-Health Index (CD-HI) as an efficient mechanism to quantify how patients with CD feel and function, and to measure key changes in a patient's multifactorial health. METHODS: We conducted semi-structured, qualitative interviews with 16 CD patients to determine the most frequent and important symptoms in CD. Based on patient responses, we designed a survey which inquired about 148 symptoms from 17 symptomatic themes. This survey was used in a cross-sectional study with 403 patients with CD recruited through the Crohn's and Colitis Foundation and IBD Partners. The collected data was used to generate the first version of the CD-HI, which contained symptom questions that had the highest impact to the population and the potential to respond to therapeutic intervention. Symptom questions were grouped into distinct symptomatic themes using factor analysis. We beta-tested the CD-HI with 15 patients with CD to evaluate its usability, clarity, and applicability. Based on patient feedback, we modified the instrument and evaluated its longitudinal reliability with 23 patients with CD. Known groups testing was performed with the final instrument. The final version of the health index is now available for use in clinical trials. RESULTS: The final version of the CD-HI contains subscales that measure the following areas of CD health: 1) fatigue, 2) dietary restrictions, 3) gastrointestinal health, 4) sleep and daytime sleepiness, 5) bowel and bladder function, 6) emotional wellbeing, 7) joint health, 8) pain, 9) neck and back health, 10) activity participation, 11) social wellbeing, and 12) skin health. Total CD disease burden is measured using a weighted composite of these subscale scores. During beta interviews, patients with CD deemed the instrument to be easy to use, clear, relevant, and comprehensive. Statistical analyses confirmed the reliability, validity, sensitivity, specificity, and internal consistency of the instrument. CONCLUSIONS: Our research demonstrates the validity of the CD-HI as a marker of disease burden in CD. This disease-specific PROM provides researchers and clinicians with a reliable tool to use in patient monitoring and clinical trials.